Amino acid modified nanocarbon composite polyacrylic acid conductive binder and preparation thereof

By using amino acid-modified nanocarbon composite polyacrylic acid conductive adhesive to form a tight three-dimensional network structure, the powdering and shedding problems caused by volume expansion of silicon carbon anode materials in lithium-ion batteries are solved, and the cycle stability and rate performance of the battery are significantly improved.

CN119662157APending Publication Date: 2025-03-21SHANGHAI UNIV

Patent Information

Application Number
CN202411869346.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, silicon-carbon negative electrode materials will expand in volume during the process of lithium ions embedded and disengagement, resulting in powdering, shedding of active particles and unstable interfaces of solid electrolytes, affecting the capacity and cycle stability of the battery.

Method used

The amino acid modified nanocarbon composite polyacrylic acid conductive adhesive is used, which consists of oxidized multi-walled carbon nanotubes, oxidized single-walled carbon nanotubes or graphene oxide, polyacrylic acid and amino acids. It is prepared by ultrasonic dispersion, dropping addition and stirring, forming a tight three-dimensional network structure to enhance adhesion and conductivity.

Benefits of technology

It improves the capacity and rate performance of the electrode, enhances the long-range bonding force with silicon-carbon active materials, improves the cycle stability and high-rate charge and discharge performance of the battery, and has self-healing characteristics and environmental protection advantages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119662157A_ABST
    Figure CN119662157A_ABST
Patent Text Reader

Abstract

The invention discloses an amino acid modified nanocarbon composite polyacrylic acid conductive binder and preparation thereof, and belongs to the field of lithium battery silicon-based negative electrode materials. The preparation method comprises the following steps: dispersing a nano-carbon material in deionized water to obtain a nano-carbon material dispersion liquid, sequentially stirring and mixing a polyacrylic acid binder and an amino acid aqueous solution, adding the nano-carbon material dispersion liquid, carrying out a heating reaction, and cooling to obtain the nano-carbon composite material. And the three-dimensional conductive adhesive which is strong in adhesive force, excellent in conductivity and capable of effectively relieving expansion stress is prepared, so that the capacity exertion and rate capability of an electrode are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium battery silicon-based negative electrode materials, and specifically relates to an amino acid-modified nano-carbon composite polyacrylic acid conductive adhesive and a preparation method thereof. Background Art

[0002] With the rapid development of portable electronic devices and electric vehicles, the demand for high-efficiency power sources has increased dramatically. Lithium-ion batteries have become the fastest-growing energy storage devices due to their advantages such as high energy density, high operating voltage, long cycle life, and no memory effect.

[0003] The performance of lithium-ion batteries depends largely on the positive and negative electrode materials that make up the battery. Silicon-carbon negative electrode materials, which are famous for their high specific capacity, have become a research hotspot in the world today because they have a theoretical specific capacity (372mAh / g) several times that of the current commercial graphite negative electrode. However, silicon-carbon negative electrode materials will undergo significant volume expansion during the process of lithium ion insertion and extraction, leading to problems such as pulverization of active particles, falling off from the current collector, and forming an unstable solid electrolyte interface (SEI), which in turn affects the capacity and cycle stability of the battery.

[0004] To address this problem, adding a binder is an effective means to buffer the volume change of the electrode during charge and discharge. At present, commercial lithium-ion batteries mainly use polyvinylidene fluoride, polyacrylic acid, carboxymethyl cellulose and styrene-butadiene rubber emulsion as binders. These binders can form covalent or non-covalent interactions with silicon-based negative electrodes, inhibiting the volume expansion of silicon-based negative electrodes to a certain extent. However, due to the poor conductivity of these binders themselves, additional conductive additives need to be added to the negative electrode material when used, resulting in reduced electrode energy density and mechanical properties, and ultimately resulting in weak long-range adhesion with the silicon-based negative electrode and conductive agent, which is not conducive to improving the long-term cycle performance and high-rate charge and discharge performance of silicon-based negative electrode lithium-ion batteries. Therefore, the development of a new type of dual-functional conductive binder is considered to be one of the important strategies to solve the problem of cycle stability of high-specific capacity negative electrode materials.

[0005] Conductive adhesive is a special adhesive that has both conductivity and adhesion. Its conductive properties can replace traditional conductive agents such as carbon black. At present, many researchers have studied the development of conductive binders. Patent CN115995557A discloses a conductive binder formed by mechanically mixing a modified carbon nanotube aqueous dispersion and an acrylic copolymer. This method improves the dispersion level of carbon nanotubes in the binder and increases the peel strength and conductivity of the electrode material. However, this physical mixing method can only provide weak hydrogen bonding and cannot effectively inhibit the expansion of the negative electrode material. It is easy to cause the material to fall off during a long cycle, affecting the electrochemical performance; Patent CN115939398A discloses a composite conductive polymer with a three-dimensional interpenetrating network structure formed by blending a polyaniline-modified carbon nanotube composite material with a polyacrylate. In this invention, aniline undergoes an oxidative polymerization reaction on the surface of the modified carbon nanotube and has excellent conductivity. This three-dimensional interpenetrating network structure conductive polymer has excellent bonding ability and electronic conductivity as a binder, but the conductive binder is an oil-based conductive binder, which is more suitable for the preparation of positive electrode sheets and cannot be applied to mainstream silicon-carbon negative electrode materials. Summary of the invention

[0006] In view of the deficiencies of the prior art, the purpose of the present invention is to prepare a three-dimensional conductive adhesive with strong bonding force, excellent conductivity and effective relaxation of expansion stress, so as to improve the capacity and rate performance of the electrode.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] An amino acid modified nano-carbon composite polyacrylic acid conductive adhesive, composed of polyacrylic acid, nano-carbon material and amino acid;

[0009] The nano-carbon material is at least one of oxidized multi-walled carbon nanotubes, oxidized single-walled carbon nanotubes and oxidized graphene;

[0010] The amino acid is at least one of glycine, histidine, arginine, threonine, glutamic acid, aspartic acid, glutamine, asparagine and lysine;

[0011] The mass ratio of the nano-carbon material to the polyacrylic acid is (0.1-2):1; the mass ratio of the amino acid to the polyacrylic acid is (0.25-2):1.

[0012] The preparation of the amino acid modified nano-carbon composite polyacrylic acid conductive adhesive comprises the following steps:

[0013] Step 1. Ultrasonically disperse the nanocarbon material in deionized water to obtain a nanocarbon material dispersion;

[0014] Step 2. Add an appropriate amount of deionized water to the polyacrylic acid binder and mix evenly, adjust the solid content of polyacrylic acid in the whole system to 2%, and drop the modifier into the above polyacrylic acid binder solution under stirring conditions. After the addition is completed, a mixed solution is obtained, and stirring is continued. The nanocarbon material dispersion is added dropwise to the mixed solution, and the mixture is heated under stirring conditions for reaction, and then cooled to room temperature to obtain a conductive adhesive.

[0015] In step 1, the concentration of the nanocarbon material dispersion is 30 mg / mL to 60 mg / mL;

[0016] In step 2, the viscosity of the polyacrylic acid binder is 10000-18000 mPa·s, the solid content is 5.8%-6.2%, and the pH is 6.5-9.0;

[0017] The modifier is an amino acid aqueous solution, wherein the amino acid concentration is 30 mg / mL to 75 mg / mL; the amino acid aqueous solution dripping speed is 5 mL / min to 8 mL / min, and the stirring speed is 300 rpm to 500 rpm;

[0018] The drop acceleration of the nanocarbon material dispersion is 3 mL / min to 6 mL / min, and the stirring speed is 500 rpm to 800 rpm;

[0019] The reaction stirring speed is 500 rpm to 1000 rpm, the heating temperature is 40 to 90° C., and the reaction time is 5 h to 10 h;

[0020] The oxidized multi-walled carbon nanotubes, oxidized single-walled carbon nanotubes and oxidized graphene are prepared by Hummers oxidation method, specifically, using multi-walled carbon nanotubes, single-walled carbon nanotubes or graphene as raw materials, concentrated sulfuric acid as solvent, potassium permanganate as oxidant, reacting at 40° C. for 1 hour, and then filtering and washing to prepare the products.

[0021] It should be noted that the polyacrylic acid used in the present invention provides good adhesion, and the abundant carboxyl groups of polyacrylic acid can form hydrogen bonds and ion-dipole interactions with the oxygen-containing groups on the surface of the silicon-carbon active material, providing numerous binding sites to maintain a close connection with the silicon-carbon active material and the current collector.

[0022] It should be noted that the carbon nanomaterial used in the present invention not only ensures high adhesion, but also realizes fast long-range transmission of electrons as a conductive skeleton, thereby improving the overall electronic conductivity of the conductive adhesive.

[0023] It should be noted that the amino acid used in the present invention is used as a modifier, and the amino groups in the amino acid are amidated with the carboxyl groups in the nanocarbon material and the polyacrylic acid to form a strong covalent bond network, thereby improving the mechanical strength of the conductive adhesive.

[0024] It should also be noted that when the conductive binder is used to make electrodes with silicon-carbon active materials, it can esterify with the hydroxyl groups on the surface of the active material through the carboxyl groups in the nanocarbon material and polyacrylic acid to form a tightly bonded three-dimensional network structure, firmly wrapping the silicon-carbon active material in the conductive three-dimensional network structure, effectively dissipating the strain energy caused by the volume fluctuation of the silicon-carbon active material, thereby improving the electrochemical performance of the electrode.

[0025] The invention provides a method for preparing an amino acid modified nano-carbon composite polyacrylic acid conductive binder. One of the innovations of the method is that a conductive additive in an electrode material is creatively introduced into the binder, thereby increasing the conductivity of the electrode material, reducing the use of the conductive additive during the preparation of the electrode material, and correspondingly increasing the use of active substances in the electrode, thereby improving the battery capacity.

[0026] The carbon nanomaterial used in the present invention is at least one of oxidized multi-walled carbon nanotubes, oxidized single-walled carbon nanotubes and oxidized graphene. When the carbon nanotubes are partially oxidized, groups such as carboxyl and hydroxyl groups are introduced on their surfaces, so that they can obtain better dispersion stability in water while maintaining electrical conductivity. At the same time, the surface groups can participate in the reaction of polyacrylic acid and amino acids to form a compact three-dimensional network structure, prevent particles from falling off the electrode and facilitate high mechanical properties.

[0027] The present invention provides a method for preparing an amino acid-modified nanocarbon composite polyacrylic acid conductive adhesive. The second innovation of the method is that the modifier amino acid is creatively introduced. Compared with the traditional physical mixing method, the nanocarbon material, amino acid and polyacrylic acid are bonded by chemical bonds to form a tight three-dimensional network structure, thereby improving the conductivity and mechanical properties of the electrode.

[0028] The present invention provides a method for preparing an amino acid-modified nanocarbon composite polyacrylic acid conductive adhesive. The third innovation of the present invention is that the conductive adhesive of the present invention has abundant polar groups such as carboxyl and amino groups. The dynamic hydrogen bond connection between the polar groups makes the adhesive have self-healing properties, which is beneficial to maintaining the structural integrity of the electrode when a huge volume change occurs during the charging and discharging process of the silicon-carbon active material.

[0029] In addition, the conductive adhesive of the present invention uses water as the solution medium throughout the process, is non-toxic and pollution-free, is beneficial to environmental protection, and conforms to the environmental protection trend. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 These are the cycle performance test results of Examples 3, 6 and Comparative Example 1.

[0031] Figure 2 These are the cycle performance test results of Examples 1, 2, 4, 5 and Comparative Example 2.

[0032] Figure 3 These are the rate performance test results of Examples 3, 6 and Comparative Example 1.

[0033] Figure 4 These are the rate performance test results of Examples 1, 2, 4, 5 and Comparative Example 2. DETAILED DESCRIPTION

[0034] In order to more clearly demonstrate the purpose, technical solutions and advantages of the present invention, the implementation process of the present invention is described below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0035] The viscosity of the polyacrylic acid binder of the present invention is 10000-18000 mPa·s, the solid content is 5.8%-6.2%, and the pH is 6.5-9.0. The present invention will be further described below by taking commercial LA136D polyacrylic acid as a binder as an example, wherein the commercial LA136D polyacrylic acid has a viscosity of 15000 mPa·s, a solid content of 6.0%, and a pH of 7.0.

[0036] The oxidized multi-walled carbon nanotubes, oxidized single-walled carbon nanotubes or oxidized graphene in the embodiments of the present invention are prepared by the Hummers oxidation method, with multi-walled carbon nanotubes, single-walled carbon nanotubes or graphene as raw materials, concentrated sulfuric acid as solvent, potassium permanganate as oxidant, reacting at 40°C for 1 hour, and then filtering and washing to obtain the obtained product.

[0037] Example 1

[0038] A preparation method of an amino acid modified nano-carbon composite polyacrylic acid conductive adhesive comprises the following steps:

[0039] (1) adding 0.3 g of oxidized multi-walled carbon nanotubes and 10 g of deionized water into a beaker, and dispersing them uniformly by ultrasonication for 20 min to obtain an oxidized multi-walled carbon nanotube dispersion;

[0040] (2) Add 0.3 g of lysine and 10 g of deionized water to a beaker to prepare a lysine aqueous solution. At room temperature, weigh 20 g of LA136D polyacrylic acid binder and 20 g of deionized water into a 250 mL three-necked flask, and drip the lysine aqueous solution into the three-necked flask at a rate of 5 mL / min under stirring at 300 rpm, then increase the stirring speed to 500 rpm, and drip the prepared oxidized multi-walled carbon nanotube dispersion at 3 mL / min. After the dripping is completed, continue to stir at a speed of 500 rpm, and heat to 90°C, keep the temperature for reaction for 5 hours, and cool to room temperature to obtain a conductive adhesive.

[0041] Weigh 7.2 g of silicon carbon 650 and add it to the above binder solution, disperse it evenly with a disperser to obtain a mixed slurry, apply the mixed slurry evenly on the copper foil with a scraper, and bake it in a vacuum oven at 120° C. for 12 hours to obtain a negative electrode sheet.

[0042] Use a punching machine to punch the negative electrode sheet, and then assemble the negative electrode into a 2032 button battery.

[0043] Example 2

[0044] A preparation method of an amino acid modified nano-carbon composite polyacrylic acid conductive adhesive comprises the following steps:

[0045] (1) adding 0.3 g of oxidized multi-walled carbon nanotubes and 10 g of deionized water into a beaker, and dispersing them uniformly by ultrasonication for 20 min to obtain an oxidized multi-walled carbon nanotube dispersion;

[0046] (2) Add 0.6 g of lysine and 20 g of deionized water to a beaker to prepare a lysine aqueous solution. At room temperature, weigh 20 g of LA136D polyacrylic acid binder and 10 g of deionized water into a 250 mL three-necked flask, and drip the lysine aqueous solution into the three-necked flask at a rate of 5 mL / min under stirring at 300 rpm, then increase the stirring speed to 500 rpm, and drip the prepared oxidized multi-walled carbon nanotube dispersion at 3 mL / min. After the dripping is completed, continue to stir at a speed of 500 rpm, and heat to 90°C, keep the temperature for reaction for 5 hours, and cool to room temperature to obtain a conductive adhesive.

[0047] Weigh 8.4 g of silicon carbon 650 and add it to the above binder solution, disperse it evenly with a disperser to obtain a mixed slurry, apply the mixed slurry evenly on the copper foil with a scraper, and bake it in a vacuum oven at 120° C. for 12 hours to obtain a negative electrode sheet.

[0048] Use a punching machine to punch the negative electrode sheet, and then assemble the negative electrode into a 2032 button battery.

[0049] Example 3

[0050] A preparation method of an amino acid modified nano-carbon composite polyacrylic acid conductive adhesive comprises the following steps:

[0051] (1) Add 1.2 g of oxidized multi-walled carbon nanotubes and 20 g of deionized water into a beaker, and disperse them evenly by ultrasonication for 20 min to obtain an oxidized multi-walled carbon nanotube dispersion;

[0052] (2) Add 0.3 g of lysine and 10 g of deionized water to a beaker to prepare a lysine aqueous solution. At room temperature, weigh 20 g of LA136D polyacrylic acid binder and 10 g of deionized water into a 250 mL three-necked flask, and drip the lysine aqueous solution into the three-necked flask at a rate of 5 mL / min under stirring at 300 rpm, then increase the stirring speed to 500 rpm, and drip the prepared oxidized multi-walled carbon nanotube dispersion at 3 mL / min. After the dripping is completed, continue to stir at a speed of 500 rpm, and heat to 90°C, keep the temperature for reaction for 5 hours, and cool to room temperature to obtain a conductive adhesive.

[0053] Weigh 10.8 g of silicon carbon 650 and add it to the above binder solution, disperse it evenly with a disperser to obtain a mixed slurry, apply the above mixed slurry evenly on the copper foil with a scraper, place it in a vacuum oven at 120° C. and bake it for 12 hours to obtain the negative electrode sheet.

[0054] Use a punching machine to punch the negative electrode sheet, and then assemble the negative electrode into a 2032 button battery.

[0055] Example 4

[0056] A preparation method of an amino acid modified nano-carbon composite polyacrylic acid conductive adhesive comprises the following steps:

[0057] (1) adding 0.3 g of oxidized multi-walled carbon nanotubes and 10 g of deionized water into a beaker, and dispersing them uniformly by ultrasonication for 20 min to obtain an oxidized multi-walled carbon nanotube dispersion;

[0058] (2) Add 0.3 g of glycine and 10 g of deionized water to a beaker to prepare a glycine aqueous solution. At room temperature, weigh 20 g of LA136D polyacrylic acid binder and 20 g of deionized water into a 250 mL three-necked flask, and drip the glycine aqueous solution into the three-necked flask at a rate of 5 mL / min under stirring at 300 rpm, then increase the stirring speed to 500 rpm, drip the prepared oxidized multi-walled carbon nanotube dispersion at 3 mL / min, continue stirring at 500 rpm after the dripping, and heat to 90°C, keep the temperature for reaction for 5 h, and cool to room temperature to obtain a conductive adhesive.

[0059] Weigh 7.2 g of silicon carbon 650 and add it to the above binder solution, disperse it evenly with a disperser to obtain a mixed slurry, apply the mixed slurry evenly on the copper foil with a scraper, and bake it in a vacuum oven at 120° C. for 12 hours to obtain a negative electrode sheet.

[0060] Use a punching machine to punch the negative electrode sheet, and then assemble the negative electrode into a 2032 button battery.

[0061] Example 5

[0062] A preparation method of an amino acid modified nano-carbon composite polyacrylic acid conductive adhesive comprises the following steps:

[0063] (1) adding 0.3 g of oxidized multi-walled carbon nanotubes and 10 g of deionized water into a beaker, and dispersing them uniformly by ultrasonication for 20 min to obtain an oxidized multi-walled carbon nanotube dispersion;

[0064] (2) Add 0.6 g of glycine and 20 g of deionized water to a beaker to prepare a glycine aqueous solution. At room temperature, weigh 20 g of LA136D polyacrylic acid binder and 10 g of deionized water into a 250 mL three-necked flask, and drip the glycine aqueous solution into the three-necked flask at a rate of 5 mL / min under stirring at 300 rpm, then increase the stirring speed to 500 rpm, drip the prepared oxidized multi-walled carbon nanotube dispersion at 3 mL / min, continue stirring at 500 rpm after the dripping, and heat to 90°C, keep the temperature for reaction for 5 h, and cool to room temperature to obtain a conductive binder.

[0065] Weigh 8.4 g of silicon carbon 650 and add it to the above binder solution, disperse it evenly with a disperser to obtain a mixed slurry, apply the mixed slurry evenly on the copper foil with a scraper, and bake it in a vacuum oven at 120° C. for 12 hours to obtain a negative electrode sheet.

[0066] Use a punching machine to punch the negative electrode sheet, and then assemble the negative electrode into a 2032 button battery.

[0067] Example 6

[0068] A preparation method of an amino acid modified nano-carbon composite polyacrylic acid conductive adhesive comprises the following steps:

[0069] (1) Add 1.2 g of oxidized multi-walled carbon nanotubes and 20 g of deionized water into a beaker, and disperse them evenly by ultrasonication for 20 min to obtain an oxidized multi-walled carbon nanotube dispersion;

[0070] (3) Add 0.3 g of glycine and 10 g of deionized water to a beaker to prepare a glycine aqueous solution. At room temperature, weigh 20 g of LA136D polyacrylic acid binder and 10 g of deionized water into a 250 mL three-necked flask, and drip the glycine aqueous solution into the three-necked flask at a rate of 5 mL / min under stirring at 300 rpm, then increase the stirring speed to 500 rpm, and drip the prepared oxidized multi-walled carbon nanotube dispersion at 3 mL / min. After the dripping is completed, continue to stir at a speed of 500 rpm, and heat to 90°C, keep the temperature for reaction for 5 hours, and cool to room temperature to obtain a conductive adhesive.

[0071] Weigh 10.8 g of silicon carbon 650 and add it to the above binder solution, disperse it evenly with a disperser to obtain a mixed slurry, apply the above mixed slurry evenly on the copper foil with a scraper, place it in a vacuum oven at 120° C. and bake it for 12 hours to obtain the negative electrode sheet.

[0072] Use a punching machine to punch the negative electrode sheet, and then assemble the negative electrode into a 2032 button battery.

[0073] Example 7

[0074] A preparation method of an amino acid modified nano-carbon composite polyacrylic acid conductive adhesive comprises the following steps:

[0075] (1) adding 0.3 g of oxidized multi-walled carbon nanotubes and 10 g of deionized water into a beaker, and dispersing them uniformly by ultrasonication for 20 min to obtain an oxidized multi-walled carbon nanotube dispersion;

[0076] (2) Add 0.3 g of lysine and 10 g of deionized water to a beaker to prepare a lysine aqueous solution. At room temperature, weigh 20 g of LA136D polyacrylic acid binder and 20 g of deionized water into a 250 mL three-necked flask, and drip the lysine aqueous solution into the three-necked flask at a rate of 5 mL / min under stirring at 300 rpm, then increase the stirring speed to 500 rpm, and drip the prepared oxidized multi-walled carbon nanotube dispersion at 3 mL / min. After the dripping is completed, continue to stir at a speed of 500 rpm, and heat to 40°C, keep the temperature for reaction for 5 hours, and cool to room temperature to obtain a conductive adhesive.

[0077] Weigh 7.2 g of silicon carbon 650 and add it to the above binder solution, disperse it evenly with a disperser to obtain a mixed slurry, apply the mixed slurry evenly on the copper foil with a scraper, and bake it in a vacuum oven at 120° C. for 12 hours to obtain a negative electrode sheet.

[0078] Example 8

[0079] A preparation method of an amino acid modified nano-carbon composite polyacrylic acid conductive adhesive comprises the following steps:

[0080] (1) adding 0.3 g of oxidized multi-walled carbon nanotubes and 10 g of deionized water into a beaker, and dispersing them uniformly by ultrasonication for 20 min to obtain an oxidized multi-walled carbon nanotube dispersion;

[0081] (2) Add 0.3 g of lysine and 10 g of deionized water to a beaker to prepare a lysine aqueous solution. At room temperature, weigh 20 g of LA136D polyacrylic acid binder and 20 g of deionized water into a 250 mL three-necked flask, and drip the lysine aqueous solution into the three-necked flask at a rate of 5 mL / min under stirring at 300 rpm, then increase the stirring speed to 500 rpm, and drip the prepared oxidized multi-walled carbon nanotube dispersion at 3 mL / min. After the dripping is completed, continue to stir at a speed of 500 rpm, and heat to 90°C, keep the temperature for reaction for 10 hours, and cool to room temperature to obtain a conductive adhesive.

[0082] Weigh 7.2 g of silicon carbon 650 and add it to the above binder solution, disperse it evenly with a disperser to obtain a mixed slurry, apply the mixed slurry evenly on the copper foil with a scraper, and bake it in a vacuum oven at 120° C. for 12 hours to obtain a negative electrode sheet.

[0083] Example 9

[0084] A preparation method of an amino acid modified nano-carbon composite polyacrylic acid conductive adhesive comprises the following steps:

[0085] (1) Add 0.3 g of graphene oxide and 10 g of deionized water into a beaker, and disperse them evenly by ultrasonication for 20 min to obtain a graphene oxide dispersion;

[0086] (2) Add 0.3 g of lysine and 10 g of deionized water to a beaker to prepare a lysine aqueous solution. At room temperature, weigh 20 g of LA136D polyacrylic acid binder and 20 g of deionized water into a 250 mL three-necked flask, and drip the lysine aqueous solution into the three-necked flask at a rate of 5 mL / min under stirring at 300 rpm, then increase the stirring speed to 500 rpm, and drip the prepared graphene oxide dispersion at 3 mL / min. After the dripping is completed, continue to stir at a speed of 500 rpm, and heat to 90°C, keep the temperature for reaction for 5 hours, and cool to room temperature to obtain a conductive adhesive.

[0087] Weigh 7.2 g of silicon carbon 650 and add it to the above binder solution, disperse it evenly with a disperser to obtain a mixed slurry, apply the mixed slurry evenly on the copper foil with a scraper, and bake it in a vacuum oven at 120° C. for 12 hours to obtain a negative electrode sheet.

[0088] Example 10

[0089] A preparation method of an amino acid modified nano-carbon composite polyacrylic acid conductive adhesive comprises the following steps:

[0090] (1) adding 0.3 g of oxidized single-walled carbon nanotubes and 10 g of deionized water into a beaker, and dispersing them evenly by ultrasonication for 20 min to obtain an oxidized single-walled carbon nanotube dispersion;

[0091] (2) Add 0.3 g of lysine and 10 g of deionized water to a beaker to prepare a lysine aqueous solution. At room temperature, weigh 20 g of LA136D polyacrylic acid binder and 20 g of deionized water into a 250 mL three-necked flask, and drip the lysine aqueous solution into the three-necked flask at a rate of 5 mL / min under stirring at 300 rpm, then increase the stirring speed to 500 rpm, and drip the prepared oxidized single-walled carbon nanotube dispersion at 3 mL / min. After the dripping is completed, continue to stir at a speed of 500 rpm, and heat to 90°C, keep the temperature for reaction for 5 hours, and cool to room temperature to obtain a conductive adhesive.

[0092] Weigh 7.2 g of silicon carbon 650 and add it to the above binder solution, disperse it evenly with a disperser to obtain a mixed slurry, apply the mixed slurry evenly on the copper foil with a scraper, and bake it in a vacuum oven at 120° C. for 12 hours to obtain a negative electrode sheet.

[0093] Comparative Example 1

[0094] A method for preparing a binder comprises the following steps:

[0095] Weigh 20 g of LA136D polyacrylic acid binder and 40 g of deionized water into a beaker and mechanically stir for 30 minutes to obtain a binder solution.

[0096] Weigh 9.6g of silicon carbon 650 and 1.2g of conductive carbon black and add them to the above binder solution (SiC650:PAA:SP=80:10:10), disperse them evenly with a disperser to obtain a mixed slurry, apply the above mixed slurry evenly on the copper foil with a scraper, and bake it in a vacuum oven at 120°C for 12h to obtain the negative electrode sheet.

[0097] Use a punching machine to punch the negative electrode sheet, and then assemble the negative electrode into a 2032 button battery.

[0098] Comparative Example 2

[0099] A method for preparing a binder comprises the following steps:

[0100] Weigh 20 g of LA136D polyacrylic acid binder and 40 g of deionized water into a beaker and mechanically stir for 30 minutes to obtain a binder solution.

[0101] Weigh 6g of silicon carbon 650 and 0.3g of conductive carbon black and add them to the above binder solution (SiC650:PAA:SP=80:16:4), disperse them evenly with a disperser to obtain a mixed slurry, apply the above mixed slurry evenly on the copper foil with a scraper, and bake it in a vacuum oven at 120°C for 12h to obtain the negative electrode sheet.

[0102] Use a punching machine to punch the negative electrode sheet, and then assemble the negative electrode into a 2032 button battery.

[0103] The negative electrode sheets obtained in the above-mentioned Examples 1-10 and Comparative Examples 1-2 were subjected to peeling tests respectively, and the peeling forces were shown in Table 1.

[0104] Table 1. Peel force test results of different embodiments and comparative examples

[0105]

[0106] From the peeling test results of Examples 3, 6 and Comparative Example 1, Examples 1, 2, 4, 5 and Comparative Example 2 in the above table, it can be seen that the adhesion strength of the conductive adhesive used in the examples is higher than that of pure PAA and carbon black used in the comparative examples. This enhanced adhesion ability is attributed to the large amount of oxygen-containing and nitrogen-containing functional groups in the amino acids and PAA molecular chains. The chemical reaction between them and other components of the electrode is relatively strong, which can more effectively enhance the deformation resistance of the electrode during the cycle charge and discharge of the battery and maintain the integrity of the electrode. By comparing the above Example 1 and Example 7, it can be seen that when the reaction temperature is reduced to 40°C, the reaction is not fully combined, resulting in a decrease in the proportion of the internal cross-linked network of the prepared adhesive, thereby reducing the peel strength of the adhesive system. By comparing the above Example 1 and Example 8, it can be seen that when the reaction time is increased to 10h, the peel strength is slightly reduced but not obvious, indicating that the increase in reaction time does not have a great effect on the degree of reaction. By comparing Example 1, Example 9 and Example 10, it can be concluded that since the oxidized multi-walled carbon nanotubes have a larger specific surface area, they can be fully mixed with other components of the binder and the active material to make the electrode sheets tighter and more uniform. Therefore, the binder peeling strength of the oxidized multi-walled carbon nanotubes is higher. However, due to its own flaky structure and the strong π-π interaction between the flaks, graphene oxide is very easy to agglomerate, which reduces its binding ability to other components of the electrode. When used, the effect is not as good as that of oxidized multi-walled carbon nanotubes and oxidized single-walled carbon nanotubes, so its peeling strength is the lowest.

[0107] The 2032-type button cells obtained in the above-mentioned Examples 3, 6 and Comparative Example 1, Examples 1, 2, 4, 5 and Comparative Example 2 were subjected to electrochemical performance tests. In the cycle test, the cells were first activated at 0.1C for 10 weeks, then at 0.2C for 10 weeks, and then the cycle performance test was performed at 0.5C. The electrochemical cycle performance is shown in FIG. Figure 1 , 2The current of 0.1C-5C is used for rate test, and the rate performance is as follows Figure 3 , 4 As shown. The results show that the battery using the conductive binder of the present invention performs better in cycle stability and rate performance, and the effect is much greater than the effect of using polyacrylic acid binder and carbon black alone. Further comparison of Examples 1, 2 and Examples 4, 5 shows that increasing the mass proportion of amino acids in the conductive binder can improve the battery cycle stability and rate performance of the pole piece. This is because the increase in the amino acid content makes the degree of cross-linking present a higher level during the reaction, and the anchor points are also increased accordingly, which maintains the stability of the active component during the cycle better. In addition, by comparing Examples 1, 3 and Examples 4, 6, it can be seen that increasing the mass proportion of oxidized multi-walled carbon nanotubes in the conductive binder significantly improves the rate performance of the pole piece. This is because the increase in oxidized multi-walled carbon nanotubes improves the conductivity of the pole piece. In the cycle performance, although the capacity has been improved to a certain extent, after the capacity suddenly drops, the capacity of the pole piece with a higher content of oxidized carbon nanotubes recovers more slowly. This is because the high mechanical strength of the oxidized carbon nanotubes affects the recovery of the binder network.

[0108] Since the conductive binder used in the embodiment has good bonding properties and excellent electron conduction ability, and the oxidized carbon nanotubes, amino acids and polyacrylic acid are bonded by chemical bonds to form a tight three-dimensional network structure, the electrochemical cycle stability and rate characteristics of the electrode prepared with the conductive binder are significantly better than those of the comparative example electrode.

Claims

1. An amino acid modified nano-carbon composite polyacrylic acid conductive adhesive, characterized in that: It is composed of polyacrylic acid, nanocarbon materials and amino acids; The mass ratio of the nano-carbon material to the polyacrylic acid is (0.1-2):1; the mass ratio of the amino acid to the polyacrylic acid is (0.25-2):

1.

2. The amino acid modified nano-carbon composite polyacrylic acid conductive adhesive according to claim 1, characterized in that: The nano-carbon material is at least one of oxidized multi-walled carbon nanotubes, oxidized single-walled carbon nanotubes and oxidized graphene; The amino acid is at least one of glycine, histidine, arginine, threonine, glutamic acid, aspartic acid, glutamine, asparagine and lysine.

3. A method for preparing the amino acid-modified nanocarbon composite polyacrylic acid conductive adhesive according to claim 1 or 2, characterized in that: The following steps are involved: Step 1. Ultrasonically disperse the nanocarbon material in deionized water to obtain a nanocarbon material dispersion; Step 2. Add deionized water to the polyacrylic acid binder and mix evenly, adjust the solid content of polyacrylic acid in the whole system to 2%, and drop the modifier into the above polyacrylic acid binder solution under stirring conditions. After the addition is completed, a mixed solution is obtained, and stirring is continued. The nanocarbon material dispersion is added dropwise to the mixed solution, and the mixture is heated under stirring conditions for reaction, and then cooled to room temperature to obtain a conductive binder.

4. The preparation of an amino acid modified nano-carbon composite polyacrylic acid conductive adhesive according to claim 3, characterized in that: In step 1, the concentration of the nano-carbon material dispersion is 30 mg / mL to 60 mg / mL.

5. The preparation of an amino acid modified nano-carbon composite polyacrylic acid conductive adhesive according to claim 3, characterized in that: In step 2, the viscosity of the polyacrylic acid binder is 10000mPa·s to 18000mPa·s, the solid content is 5.8% to 6.2%, and the pH is 6.5 to 9.

0.

6. The preparation of an amino acid modified nano-carbon composite polyacrylic acid conductive adhesive according to claim 3, characterized in that: In step 2, the modifier is an amino acid aqueous solution, wherein the amino acid concentration is 30 mg / mL to 75 mg / mL; the amino acid aqueous solution is added at a dripping speed of 5 mL / min to 8 mL / min, and the stirring speed is 300 rpm to 500 rpm.

7. The preparation of an amino acid modified nano-carbon composite polyacrylic acid conductive adhesive according to claim 3, characterized in that: In step 2, the drop acceleration of the nano-carbon material dispersion is 3 mL / min to 6 mL / min, and the stirring speed is 500 rpm to 800 rpm.

8. The preparation of an amino acid modified nano-carbon composite polyacrylic acid conductive adhesive according to claim 3, characterized in that: In step 2, during the reaction, the stirring speed is 500 rpm to 1000 rpm, the heating temperature is 40 to 90° C., and the reaction time is 5 h to 10 h.

Citation Information

Patent Citations

  • Carbon nano-tube plastic electric-conduction composite material and wet preparation process thereof

    CN110467782A

  • Preparation method of conductive binder, battery pole piece and battery

    CN115995557A

  • Water-based single-walled carbon nanotube conductive paste and preparation method and application thereof

    CN116435513A

  • Polymeric binder for anodes using interaction between polyacrylic acid and polyaniline

    KR1020180048554A

Cited By

  • Conductive binder and preparation method thereof, electrode slurry, electrode and lithium ion battery

    CN122381740A